A Geography of Reading in 'Paris, Port-de-Mer' - Jay Bochner (Studies in 20th & 21st Century Literature, 1979)
«Paris, Port-de-Mer» is chosen purposely for its apparent lack of focus as an example of the difficulty of reading the author's later work. The way into the text is made twice, once via the presumed topic of Paris as a seaport, once with the help of Descartes' Discours de la méthode, which supplies the terms for various metaphors operating in the narrative. The topic quickly goes underground, only to emerge after it is understood that the many books and libraries are to be treated somewhat like the port, places of arrival and departure, but not of permanence. The text is similarly a port, or «trace», as Cendrars calls it. The narrative is an inventory of books, but at the same time a departure from them. The «most beautiful library of the world,» though never explicitly named as such, is no doubt the bookstalls on the quais, and the narrator as reader is, at his best, peripatetic.
Keywords: Blaise Cendrars; Paris Port de Mer; geography; René Descartes